P. 1
Essay Complex Analysis

Essay Complex Analysis

|Views: 3,072|Likes:
Published by Khoa Võ
Complex Analysis in One Variable
Complex Analysis in One Variable

More info:

Categories:Types, School Work
Published by: Khoa Võ on Jul 01, 2012
Copyright:Traditional Copyright: All rights reserved

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

06/05/2013

pdf

text

original

EXPANSIONS

In this section, the exercises will be shown are 1, 2, 3, 4, 5, 7, 8, 11, 12, 15, 16, 19, 23.

Exercise 5.17. (E. 1, E. 2, E. 3, E. 4 P. 274)

The following exercises involve our generating a new Taylor series through a change of variables

in the geometric series Eq.(5.2-8) or some other familiar expansion. Here a is any constant.

Explain how the following are derived

1. 1

1 + az = 1−az + a2

z2

−a3

z3

+ ...

|z| <

1

a


2. 1

1 + z2 = 1−z2

+ z4

−z6

+ ... (|z| < 1)

3. 1

1 + a + z = 1−(z + a) + (z + a)2

−(z + a)3

+ ... (|z −a| < 1)

4.

a) e−z2

= 1−z2

+ z4

2 − z6

6 + ... all z

b) Use the preceding result to find the 10th derivative of e−z2

at z = 0.

Solution.

1. Because of |z| <

1

a

, we get

1

1 + az =

1

1−(−az)

=

∞ n=0

(−az)n

2. We use the formular

1

1 + w = 1−w + w2

−w3

+ ...,|w| < 1

And set w = z2

. we can infer

1

1 + z2 = 1−z2

+ z4

−z6

+ ...,|z| < 1

3. In a similar fashion, we also use the formular

1

1−w = 1 + w + w2

+ w3

+ ...,w < 1

We can deduce that

1

1 + a + z = 1−(z + a) + (z + a)2

−(z + a)3

+ ...

155

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

for |−a−z| < 1 or |z + a| < 1

4.

a) The formular is ew

= 1 + w + w2

2! + ... for all w

Then with w = −z2

, we replace into this formular and get

e−z2

= 1 +−z2

+ z4

2! − z6

3! + z8

4! −...

b) Apply Taylor series expansion, we see the general coefficient is cn = f(n)

(z0)

n!

So with z0 = 0, we have

f(n)

(0) = cnn!

Hence, the coefficient of z10

is −1

5! in the series of (a)

Thus f(10)

(0) = −10!

5! = 30240

Exercise 5.18. (E. 5, E. 7, E. 8 P. 274)

1. Differentiate the series of equation 5.5-2 to show that

1

z3 = 1− 3.2

2 (z−1) + 4.3

2 (z−1)2

− 5.4

2 (z−1)3

+ ...,|z−1| < 1

2. Use the series in equation 5.2-8 and successive differentiation to show that, for N ≥ 0

1

(1−z)N =

∞ n=0

cnzn

,cn = (N −1 + n)!
n!(N −1)! ,|z| < 1

3. Integrate the series of Exercise 2 along a contour connecting the origin to an arbitrary

point z, where |z| < 1 to show that

tan−1

z =

∞ n=0

(−1)n z2n+1

2n + 1,|z| < 1

Solution.

1. We can divide it as follows

156

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

1

z3 = 1
z2

.z,|z−1| < 1

=

∞ n=0

(n + 1)(1−z)n

∞ n=0

(1−z)n

∞ n=0

(n + 2)(n + 1)

2

(1−z)n

This series express as the right side in the proof.

2. In equation 5.2-8, we have

∞ j=1

zj−1

= 1 + z + z2

+ ... = S (z) = 1

1−z,|z| < 1

Successive differentiation is that

1

(1−z)N = z0

+ N!

(N −1)!z + (N + 1)!
(N −1)!2!z2

+ (N + 2)!
(N −1)!3!z3

+ ...

=

∞ n=0

(N −1 + n)!

n!(N −1)! zn

where |z| < 1.

3. We observe the formular below

1

1 + w2 = 1−w2

+ w4

−w6

+ ...,|w| < 1

And with |z| < 1, we have

ˆ 0

z

1

1 + w2dw =

ˆ 0

z

1−w2

+ w4

−w6

+ ...

dw

= z − z2

3 + z5

5 − z7

7 + ...

Then

ˆ 0

z

1

1 + w2dw = tan−1

z

Thus tan−1

z =

∞ n=0

(−1)n z2n+1

2n + 1 with |z| < 1.

157

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

Exercise 5.19. (E. 11 P. 276)

By considering the first and second derivatives of the geometric series in Equation 5.2–8, show

that

∞ n=1

n2

zn

=

z + z2
(1−z)3

for |z| < 1

Solution.

In equation 5.2-8, we have had

∞ j=1

zj−1

= 1 + z + z2

+ z3

+ z4

+ z5

+ ... = 1

1−z,|z| < 1

Successive differentiation the first time, we obtain

−1
(1−z)2 = 1 + 2z + 3z2

+ 4z3

+ 5z4

+ 6z5

+ ...

Successive differentiation the second time, we get

2

(1−z)3 = 2 + 6z + 12z2

+ 10z3

+ ...

We compute the following series

z

(1−z)2 = z + 2z2

+ 3z3

+ 4z4

+ ... =

∞ n=1

nzn

2z

(1−z)3 = 2z + 6z2

+ 12z3

+ 20z4

+ ... =

∞ n=1

n(n + 1)zn

So

2z

(1−z)3 − z

(1−z)2 = 2z−z(1−z)

(1−z)3 = z2

+ z

(1−z)3 =

∞ n=1

n(n + 1)zn

∞ n=1

nzn

=

∞ n=1

n2

zn

Obtain the following Taylor expansions. Give a general formula for the nth coefficient, and

state the circle within which your expansion is valid.

Exercise 5.20. (E. 12 P. 276)

Use series multiplication to find a formula for cn in these Maclaurin expansion. In what circle

is each series valid?

coshz

1−z =

∞ n=0

cnzn

Solution.

We have that for all z then

coshz = 1 + z2

2! + z4

4! + z6

6! + ...

158

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

And with |z| < 1

1

1−z = 1 + z + z2

+ z3

+ ...

Then we multiply them and get

coshz

1−z =

1 + z2

2! + z4

4! + z6

6! + ...

1 + z + z2

+ z3

+ ...

=

∞ n=0

cnzn

= 1 + z +

1 + 1
2!

z2

+

1 + 1
2!

z3

+

1 + 1

2! + 1
4!

z2

+ ...

Hence, the general coefficient is

cn =

1 + 1

2! + 1

4! + ... + 1
n!

,neven

1 + 1

2! + 1

4! + ... + 1

(n−1)! ,nodd

Exercise 5.21. (E. 15, E. 16, E. 19, E. 23 P. 276)

Obtain the following Taylor expansions. Give a general formula for the nth coefficient, and state

the circle within which your expansion is valid.

1.

z

(z−1)(z + 2) expanded about z = 0

2. z + 1
(z−1)2

(z + 2)

expanded about z = 2

3. 1

z3 expanded about z = i

4. z3

+ 2z2

+ z−1

z2

−4 expanded about z = 1

Solution.

1. We have, from Rule I,

f (z) =

z

(z −1)(z + 2)

= A

(z −1) + B

(z + 2)

= z(A + B) + 2A−B
(z−1)(z + 2)

We obtain a system of equations

159

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

A + B = 1

2A−B = 0

Then we get the root is

A = 1
3

B = 2
3

Thus f (z) be rewritten

f (z) = 1
3

1

z −1 + 2
3

1

z + 2

Then, we see 2 familiar series below.

1

3

1

z−1 = −1
3

1 + z + z2

+ z3

+ ...

= −1
3

∞ n=0

zn

2

3

1

z + 2 = 2
3

1

1 + z
2

= 2
3

∞ n=0

(−1)n

2−n

zn

We can infer

f (z) = −1
3

∞ n=0

zn

+ 2
3

∞ n=0

(−1)n

2−n

zn

=

∞ n=0

−1

3 + 2

3 (−1)n

2−n

zn

2. In a similar way, we get

2

z + 2 = 2

z−1 + 3 =

2

3

1 + z−1
3

= 2
3

1− z−1

3 +

z−1
3

2

−...

− 1

z + 1 = − 1

z−1 + 2 =

−1
2

1 + z−1
2

= −1
2

1− z−1

2 +

z −1
2

2

−...

Add the two previous series

z

(z + 1)(z + 2) =

∞ n=0

cn (z−1)n

where cn = −1
2

−1
2

n

+ 2
3

−1
3

n

160

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

3. We have

f (z) =

z + 1

(z−1)2

(z + 2)

= A

(z −1) + B

(z −1)2 + C

(z + 2)

= A(z−1)(z + 2) + B (z + 2) + C (z −1)2
(z−1)2

(z + 2)

= z2

(A + C) + z(A + B −2C)−2A + 2B + C

(z−1)2

(z + 2)

Let the numerator be equal to z + 1 and we get A = 1

9 , B = 2

3 , C = −1
9

Hence,

f (z) = 1

9. 1

(z−1) + 2

3. 1

(z−1)2 − 1

9. 1
(z + 2)

Then

1

9. 1

(z−1) = 1

9. 1
(1 + z−2) = 1

9.

∞ n=0

(−1)n

(z−2)n

,|z−2| < 1

2

3. 1

(z −1)2 = 2

3. 1
(1 + z−2)2 = 2

3.

∞ n=0

(−1)n

(n + 1)(z−2)n

,|z−1| < 1

−1

9. 1

(z + 2) = −1

9. 1
(4 + z −2) = − 1
36

1

1 + z−2
4

= − 1

36.

∞ n=0

(−1)n

4−n

(z−2)n
,

z−1

4

<

1

We can infer

f (z) =

∞ n=0

cnzn

where cn = 1

9.(−1)n

+ 2

3.(−1)n

(n + 1)− 1

36.(−1)n

4−n

4. We see that

f (z) = z3

+ 2z2

+ z−1

z2

−4 = (z−1) + 3 + 5z + 7
z2

−4

And analyse that

5z + 7

z2

−4 = A

(z + 2) + B

(z−2)

= z(A + B)−2A + 2B
z2

−4

161

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

Let the numerator equal to 5z + 7 and we get A = 3

4 , B = 17
4

Then

5z + 7

z2

−4 = 3

4. 1

(z + 2) + 17

4 . 1

(z−2)

3

4. 1

(z + 2) = 1

4. 1

1 + z−1
3

=

∞ n=0

1

4.(−1)n

. 1

3n.(z −1)n

,|z−1|<3

17

4 . 1

(z−2) = −17

4 . 1
(1−(z−1)) =

∞ n=0

−17

4 .(z−1)n

,|z−1|<1

We can infer

f (z) =

∞ n=0

cn (z−1)n

where cn = 1

4.(−1)n

. 1

3n − 17
4

162

5 INFINITE SERIES INVOLVING A COMPLEX VARIABLE

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->